2015
DOI: 10.1007/s00464-015-4707-7
|View full text |Cite
|
Sign up to set email alerts
|

A matched cohort analysis of single anastomosis loop duodenal switch versus Roux-en-Y gastric bypass with 18-month follow-up

Abstract: LDS has comparable weight loss results to GBP. However, LDS has fewer 30-day and 18-month complications and patients suffer from less nausea postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 26 publications
1
29
0
3
Order By: Relevance
“…In this study, the 2-year follow-up is important since the nadir of weight loss after DS is at 18 months statistically; thus, we are reporting the maximum weight loss a revisional DS patient can experience after this surgery. However, a vital point of this paper is the fact that this procedure has very good weight loss, but it in no way approaches the weight loss seen when SADS or RYDS are done as a primary procedure [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the 2-year follow-up is important since the nadir of weight loss after DS is at 18 months statistically; thus, we are reporting the maximum weight loss a revisional DS patient can experience after this surgery. However, a vital point of this paper is the fact that this procedure has very good weight loss, but it in no way approaches the weight loss seen when SADS or RYDS are done as a primary procedure [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 97%
“…Recently, there have been several reports on the outcomes of SADI-S procedure [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. One of the articles published by Neichoy et al [16] on the midterm outcomes of SADI-S reported EWL of 88% at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it decreases the technical complexity associated with duodenal switch without compromising outcomes. Cottam et al [30] published a matched cohort between SADI-S and RYGB with 18-month follow-up and found the weight loss profile to be similar between the 2 procedures. While the complication rates were lower with SADI-S [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have called this modification "stomach intestinal pylorus sparing" (SIPS) surgery to help differentiate it from the common complication of the traditional Roux-en-Y duodenal switch. The preservation of more intestine, along with the ileocecal valve, reduces the risk for malnutrition and diarrhea often associated with the duodenal switch [3,4]. The lack of a distal small bowel enteroenterostomy should eliminate or decrease the chances of internal hernias.…”
mentioning
confidence: 99%